Unlogic Birth Education, Perceived Husband Assertiveness, and Mode of Delivery: A Retrospective Observational Study - Nur Alima Amelia; Ummu Khuzaimah (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
The increasing rate of caesarean section has raised concerns about childbirth interventions performed without clear medical indications. Antenatal education may support childbirth preparation and informed decision-making, although the mechanisms linking such education to mode of delivery remain uncertain. This study examined the association between participation in the Unlogic Birth (UB) educational program and mode of delivery and assessed whether perceived husband assertiveness mediated this association. A retrospective observational study was conducted among 72 postpartum women who had received antenatal care at Klinik Utama Cikal Mulia, Jakarta, Indonesia. Participants were selected using purposive sampling and classified according to their participation in UB education. Perceived husband assertiveness was measured using a 12-item questionnaire completed by wives, while mode of delivery was verified through clinical records. Direct and indirect associations among the variables were examined using an exploratory structural-path analysis. Of the 72 participants, 58 had participated in UB education and 14 had not. All UB participants experienced vaginal birth, whereas 13 of the 14 non-participants underwent caesarean section. UB participation was significantly associated with mode of delivery (T = 27.27, p < 0.05). However, UB participation was not significantly associated with perceived husband assertiveness (T = −0.38, p > 0.05), and perceived husband assertiveness was not significantly associated with mode of delivery (T = 0.96, p > 0.05). The proposed mediating pathway was therefore not supported. The findings should be interpreted cautiously because of the retrospective design, purposive sampling, unequal group sizes, absence of detailed baseline comparisons, and limited variability in perceived husband assertiveness.